2022
DOI: 10.3332/ecancer.2022.1359
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and perspective of cancer patients during the COVID-19 pandemic and the Lebanese financial crisis: a multicentric cross-sectional study

Abstract: Lebanese cancer patients are facing a war on two fronts, between the COVID-19 pandemic and one of the most severe financial crises globally in recent times. This multicentric cross-sectional study was conducted, aiming to analyse challenges and perspective of this particularly vulnerable population. A questionnaire was prepared to assess socio-demographic data, challenges faced during the pandemic, perspectives concerning cancer and COVID-19, a scale was also validated to assess knowledge level regarding COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Similarly, to our findings, the authors reported that the majority of patients expressed a greater fear of cancer than COVID-19, and encountered transportation challenges to and from the hospital. However, while in our study participants agreed that precautionary measures in both private and public hospitals were very well implemented, Nawfal et al [7] reported that approximately a quarter of participants experienced difficulty in maintaining precautionary measures in both private and public hospitals. This difference might be related to differing practices and standards between medical centres.…”
Section: Comparison To Other Studiescontrasting
confidence: 65%
See 1 more Smart Citation
“…Similarly, to our findings, the authors reported that the majority of patients expressed a greater fear of cancer than COVID-19, and encountered transportation challenges to and from the hospital. However, while in our study participants agreed that precautionary measures in both private and public hospitals were very well implemented, Nawfal et al [7] reported that approximately a quarter of participants experienced difficulty in maintaining precautionary measures in both private and public hospitals. This difference might be related to differing practices and standards between medical centres.…”
Section: Comparison To Other Studiescontrasting
confidence: 65%
“…Nawfal et al [ 7 ] conducted a survey study exploring the same question addressed in our research but focusing on other medical centres around Lebanon. Similarly, to our findings, the authors reported that the majority of patients expressed a greater fear of cancer than COVID-19, and encountered transportation challenges to and from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded these medications, in part, because treatment most commonly occurs in infusion centers. However, there have been PLOS GLOBAL PUBLIC HEALTH documented shortages in both oncology drugs and associated palliative and supportive drugs, which should be further explored [21]. Secondly, when calculating mean monthly income estimates for August 2021 and April 2023, we assumed a fixed dollar amount compared to January 2022 (see methods), despite ongoing devaluation of salaries in USD.…”
Section: Discussionmentioning
confidence: 99%
“…Financial toxicity associated with cancer care negatively impacts both cancer patients themselves and their families, who may be forced to make financial sacrifices to cope with cancer costs [3]. The COVID-19 pandemic has undeniably worsened the financial challenges faced by people living with cancer, particularly in the low-and middle-income countries (LMICs) [4,5].…”
Section: Introductionmentioning
confidence: 99%